2021
DOI: 10.3390/brainsci11070945
|View full text |Cite
|
Sign up to set email alerts
|

Minor Non-Disabling Stroke Patients with Large Vessel Severe Stenosis or Occlusion Might Benefit from Thrombolysis

Abstract: Background: The benefit of alteplase in minor non-disabling acute ischemic stroke (AIS) is unknown. We aimed to explore the clinical efficacy of alteplase-treatment in minor non-disabling stroke in clinical practice. Methods: We used a prospectively collected database of AIS patients who were being assessed for thrombolysis with alteplase. Minor non-disabling AIS was identified as patients with baseline National Institutes of Health Stroke Scale (NIHSS) score ≤ 5 and a score 0 or 1 on each baseline NIHSS score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Eighteen studies 16,17,22–37 provided data on mRS scores of 0 to 1 at 90 days (Figure 2). Rates of excellent functional outcome in the IVT compared with BMT group revealed no significance (2252/2717, 82.89% versus 3295/4073, 80.90%, P =0.274; Table).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen studies 16,17,22–37 provided data on mRS scores of 0 to 1 at 90 days (Figure 2). Rates of excellent functional outcome in the IVT compared with BMT group revealed no significance (2252/2717, 82.89% versus 3295/4073, 80.90%, P =0.274; Table).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies 26,29,33 provided data on hemorrhagic transformation (Figure 3). There was a higher rate of hemorrhagic transformation in the IVT group compared with BMT group (68/1036, 6.56% versus 10/648, 1.54%, P <0.001; Table), as well as higher odds of hemorrhagic transformation with IVT, with no heterogeneity (OR, 4.73 [95% CI, 2.40–9.34]; I ²=0%, P =0.987).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, minor non‐disabling stroke was defined as patients with baseline NIHSS score ≤5 and a score of 0 or 1 on each baseline NIHSS score item (items 1a to 1c being 0). 25 However, these findings need to be verified in future randomized trials. We did not find a significant association between intravenous t‐PA and excellent outcome in disabling subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…It showed that patients with such characteristics could benefit from intravenous alteplase. In the study, minor non‐disabling stroke was defined as patients with baseline NIHSS score ≤5 and a score of 0 or 1 on each baseline NIHSS score item (items 1a to 1c being 0) 25 . However, these findings need to be verified in future randomized trials.…”
Section: Discussionmentioning
confidence: 99%